The Effects of Total Physical Response-Story Telling to Teach Vocabulary to Improve Elementary Students’ Vocabulary Achievement - Luh Arumdiah Rosita Dewi (Magister Scientiae, 2010)
Having sufficient vocabulary is very important in order to be able to listen, speak, read and write. However, many teachers still neglect it. As a result, many students get difficulty in improving their language skills because of the limited number of vocabulary items they have acquired. Because of that, it is important to enrich students’ vocabulary achievement by implementing an effective technique to teach vocabulary. This study was conducted to find out the effectiveness of Total Physical Response-Story Telling to teach vocabulary to improve Elementary students’ vocabulary achievement. It was a quasi-experimental study. The writer used two groups, pretest-posttest design. The experimental group was taught by using Total Physical Response-Story Telling (TPR-S) while the control group was taught by using translation. The research instrument in this study was the vocabulary test that consisted of 50 multiple-choice items that the students had to finish in 90 minutes. Then, she set the level of significance which was 0.05. Finally, she analyzed the data by using Mann Whitney U Test. From the results of the research, it showed that TPR-S gave significant influence to improve students’ vocabulary development. The students who were taught by using TPR-S obtained higher vocabulary achievement than those who were taught by using translation. Therefore, the research suggested to the teachers of “MIMI” Elementary School use TPR-S as their teaching technique to teach vocabulary in their classroom. It also suggested the students not only to review the new vocabulary they have learned but also to apply it in their daily life so that they will not forget it easily.